Analogs of the spherical transform on the hyperbolic plane - Vasilyanskaya, V. S.; Volchkov, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We introduce the notion of “s”-convolution on the hyperbolic plane H^2 and consider its properties. Analogs of the Helgason spherical transform on the spaces of compactly supported distributions in H^2 are studied. We prove a Paley –Wiener – Schwartz-type theorem for these transforms.